(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Autoinflammatory diseases (AInDs) are a variant of autoimmune diseases (AIDs) because they are also characterised by inflammation without an aetiological factor, are associated with immune response genes, and are amenable to immunosuppressive therapy [1,4,6,7].